A deputy’s request for information containing bank secrecy in Ukraine: an urgent issue of the present (Law and Safety, 2023)
The article is devoted to the study of the peculiarities of a People’s Deputy of Ukraine’s request to banking institutions with the purpose of obtaining information containing bank secrecy.It is emphasized that today information is an important resource for socio-economic, technological and cultural development. In addition, information is defined as the most important civilisational value and has a dominant status. Considering this, the institute of bank secrecy is a mandatory attribute of the legal system of the State, the content of which is determined by the peculiarities of economic and legal doctrine and the formation of the regulatory framework. The author analyses the system of legal acts which regulate the proper functioning of the legal regime of banking secrecy. The main ways in which banks are obliged to ensure the preservation of bank secrecy are identified. Attention is focused on the regulatory framework that establishes an comprehensive list of grounds for obtaining information containing bank secrecy and the bodies entitled to receive such information.The two main positions on the need to provide the People’s Deputies with the right to obtain information constituting bank secrecy are outlined. Representatives of the first position focus on the fact that People’s Deputies should not have access to bank secrecy; the representatives of the second one, on the contrary, justify their position by the necessity and competence of People’s Deputies to receive such information. Each of the parties relies on the current legislation of Ukraine to argue its views. The final point on the resolution of this issue was established only by the decision of the Constitutional Court of Ukraine.It has been established that the possibility of a request by a People’s Deputy of Ukraine to a banking institution to obtain confidential information is provided for in the current legislation, but only within clearly defined limits, namely: the information is necessary for the legislative work; the issues under consideration and related to obtaining such information should be within the powers of the Verkhovna Rada of Ukraine.It is noted that a request to banking institutions to obtain information with restricted access under a certain procedure may be submitted either individually or through the activities of the Verkhovna Rada of Ukraine committees.
Keywords: People’s Deputy of Ukraine; bank secrecy; National Bank of Ukraine; Constitutional Court of Ukraine; deputy’s request; information with restricted access; Verkhovna Rada of Ukraine.